ISOLATION AND SCREENING OF ACTIVE CULTURES OF LACTIC ACID BACTERIA FOR INCLUSION IN THE COMPOSITION OF THE STARTER IN THE PREPARATION OF CHEESE FROM WHEY - Tynybayeva , I.K.; Zhakupova , G.N.; Tultabayeva , T.Ch.; Nurtayeva , A.B.; Sagandyk, A.T.; Bekbay , S.K.; Sarmurzina , Z.S. (Eurasian Journal of Applied Biotechnology, 2022)
The starter cultures used to develop fermented milk products play a critical role in ensuring the quality of the final product in terms of organoleptic properties, nutritional value, and storage. The quality of the product depends on the strain and is due to differences between strains in the presence and activity of metabolic pathways. The selection of competitive bacterial cultures and the development of bacterial starters are fundamental to establishing and maintaining industrial microorganism collections. The process of creating bacterial starters takes a lot of time and includes the main stages of work: the isolation of microbes from various sources, their development, the selection of promising strains with industrially active properties, and the subsequent isolation of pure cultures as part of a consortium of bacterial starters. Potential probiotics were isolated from samples of fermented milk products - cottage cheese, butter, etc. home-made in the Akmola region, then identified and characterized. In this study, new probiotic bacteria were selected with high antibacterial activity against pathogenic microorganisms for humans and sensitivity to antibiotics. 4 strains of the studied isolates showed resistance to antibiotics and test strains. As a result of identification by MALDI-TOF MS-biotyping, it was found that the isolates isolated from domestic fermented milk products belong to the species Leuconostoc mesenteroides, Enterococcus faecium 2 pcs, Lactobacillus paracasei.